Factores que influyen en la ingesta alimentaria de pacientes en diálisis peritonial del Hospital Guillermo Almenara Irigoyen, 2011 - Serrano Luján, Claudia (2019)
Objective: The aim of this study was to assess dietary intake of PD patients and to determine the intake with a variety of factors that can influence it. Methodology: We evaluated 20 PD patients of Guillermo Almenara Hospital,without any exclusion criteria. Nutritional assessment was complete, including major symptoms of the disease asdialysate solution, diuresis, anthropometry (BMI, PCT, WBC), level of úrea, nutritional history, analysis of dietaryintake by food frequency questionnaire, food, registration of dietary intake of 3 days and use of food compositiontable of Peru (2009). It was also considered a brief assessment of the economic and psychological availability, forall this relate to the situation of the intake. Results: Of the 20 patients, 12 were men and 8 women, mostly 35 to 60years. Protein intake was recorded 30% indicating a poor dietary intake. Indirect relationships were found betweenuremia and dialysis, with dietary intake (r = -0.38 and -0.2, respectively). By chi-square test found no dependencebetween depressive and intake level (sig. 0.77). Conclusion: These patients have deficiencies of protein, mainly vitamins and minerals in your dietary intake. For this group of patients, the factors that influence intake were: uremia,dialysis, and economic availability